2021
DOI: 10.21776/ub.jfmr.2021.005.01.16
|View full text |Cite
|
Sign up to set email alerts
|

HEMOCYTE PROFILE OF SUSUH KURA (Sulcospira Testudinaria) IN ORDER TO EVALUATE THE WATER QUALITY OF BADHER BANK CONSERVATION AREA, TAWANGREJO VILLAGE, BINANGUN DISTRICT, BLITAR

Abstract: Kawasan Konservasi Badher Bank merupakan kawasan konservasi yang terfokus dalam konservasi Ikan Badher yang merupakan ciri khas di daerah tersebut. Tujuan dari penelitian ini untuk menganalisis profil hemosit Susuh Kura (Sulcospira testudinaria) di Kawasan Konservasi Badher Bank dan menganalisis kualitas air dalam rangka evaluasi kualitas perairan. Metode penelitian yang digunakan adalah deskriptif dengan teknik survei. Sampel yang diambil adalah sampel kualitas air dan susuh kura di 4 stasiun. Berdasakan hasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Initially, the distinction between hyalinocytes and granulocytes was made based on morphological parameters, years later it has been confirmed that there are also functional differences between both haemolymph cell types after analysis of metabolic and functional parameters (122,221). Recently, research efforts are focusing on revealing dissimilar immune functions among marine invertebrate haemocyte subpopulations, for example in ascidians (222); crustaceans as shrimps (223)(224)(225)(226)(227)(228), lobsters (229) and crabs (230); gastropod molluscs as sea snails (231)(232)(233)(234), abalones (235) and sea hares (236); and bivalve molluscs as oysters (182,216,237,238). This review focuses on the major findings in functional differences between the main bivalve haemocyte types.…”
Section: Functional Differences Between Hyalinocytes and Granulocytesmentioning
confidence: 99%
“…Initially, the distinction between hyalinocytes and granulocytes was made based on morphological parameters, years later it has been confirmed that there are also functional differences between both haemolymph cell types after analysis of metabolic and functional parameters (122,221). Recently, research efforts are focusing on revealing dissimilar immune functions among marine invertebrate haemocyte subpopulations, for example in ascidians (222); crustaceans as shrimps (223)(224)(225)(226)(227)(228), lobsters (229) and crabs (230); gastropod molluscs as sea snails (231)(232)(233)(234), abalones (235) and sea hares (236); and bivalve molluscs as oysters (182,216,237,238). This review focuses on the major findings in functional differences between the main bivalve haemocyte types.…”
Section: Functional Differences Between Hyalinocytes and Granulocytesmentioning
confidence: 99%